Exploring chronic airways disease patients' perspectives on self-management topics. Issue 12 (December 2022) - McMillan, Austin; Tregobov, Noah; Shum, Jessica; Christie, Ian; Akhtar, Alizeh; Poureslami, Iraj; ,
Abstract: Objectives: In this study, we explored chronic airways disease (CAD) patients' responses to health literacy (HL) communication domain questions within disease self-management scenarios, as part of a larger CAD HL measurement tool development study. Methods: Adult asthma and chronic obstructive pulmonary disease (COPD) patients from specialty care respiratory clinics were initially presented with realistic disease management scenarios and asked to share information they would communicate. Participants' responses were grouped into response categories that were reviewed and verified by key informants. A new cohort of CAD patients then responded to the same scenarios and had their answers placed into the developed response categories by trained interviewers. Results: 19 initial stage participants' responses informed response categories for the following self-management topics: Inhaler Use (n = 20); Prednisone Use (n = 30); Flu (Influenza) (n = 35); and Weather Forecasting & Air Quality Index (n = 29). 141 participants' responses were categorised during the second stage. Conclusions: Specialty care CAD patients displayed an understanding of key information to communicate across disease self-management topic. Our two-step, patient-driven approach may interest researchers investigating health-related communication from patients' perspectives. Practice implications: Findings may illuminate potential areas to investigate communication gaps among CAD patients; further investigation is warranted among non-specialty care patients. Highlights: Chronic airways disease patients generally understand disease management issues. Inhaler differences and technique are areas to emphasize in patient encounters. Medication interactions with vaccines and other medications should be discussed. Personalized communication with healthcare providers may be beneficial.